Oxidant – antioxidant status and some biochemical parameters in pregnant and non pregnant Iraqi she camels - AL-Zamely, Hayder A.N. (The Iraqi Journal of Veterinary Medicine, 2011)
This study was carried out to determine the changes in oxidant – antioxidant status and some biochemical parameters in pregnant Iraqi female camels in comparison with non pregnant one. To determine this objective (30) blood samples from pregnant female camels and (30) blood samples from non pregnant female camels was taken at last state of pregnancy (number of animals are 30 in each group) , blood samples were put in the test tubes contain anticoagulant (EDTA) , after centrifugation serum samples were taken for measurement of Malondialdehyde (MDA) , albumin , uric acid , total protein , alkaline phosphatase and urea concentrations.The results revealed significant increase (P < 0.05) in malon dialdehyde concentration in pregnant female camels in comparison with non pregnant. Also the results were showed insignificant decrease in albumin concentration and significant increase (P <0.05) in uric acid concentration in pregnant group which may be due to its antioxidant activity against lipid peroxidation during pregnancy. In related to the biochemical parameters the results were showed significant decrease (P <0.05) in the total protein of pregnant female camels which may be due to decrease in albumin concentration, while there is significant increase (P <0.05) in ALP.